1999
DOI: 10.1108/09576059910256286
|View full text |Cite
|
Sign up to set email alerts
|

Information systems and other capital investments: evaluation practices compared

Abstract: Reports on the findings of two surveys which examined the way organisations evaluate information systems/technology and other capital of investments. The issues addressed include the following: the extent of evaluation; the extent to which evaluation depends on organisational factors, such as project cost and level of organisational turnover; the existence of formal procedures of evaluation; the financial and other criteria used to evaluate investments, and their importance; and the problems organisations face… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(49 citation statements)
references
References 15 publications
1
47
1
Order By: Relevance
“…Regardless, Ballatine and Stray [3,4], and Lefley [38] report the use of traditional appraisal techniques during the evaluation of IT although, argue that such methods have become obsolete and inappropriate. In doing so, discouraging long-term strategically important projects that typically offer intangible and non-financial benefits.…”
Section: Limitations Of Traditional Appraisal Techniquesmentioning
confidence: 99%
“…Regardless, Ballatine and Stray [3,4], and Lefley [38] report the use of traditional appraisal techniques during the evaluation of IT although, argue that such methods have become obsolete and inappropriate. In doing so, discouraging long-term strategically important projects that typically offer intangible and non-financial benefits.…”
Section: Limitations Of Traditional Appraisal Techniquesmentioning
confidence: 99%
“…It is challenging for managers when they have to choose the most appropriate evaluation approach to use, but it is essential that stakeholders' opinions are considered and that decisions are not made entirely from a traditional financial perspective. Ballantine et al (1999) found that half of the organizations that they investigated had no formal evaluation procedures. Gunasekaran et al (2001) argue that there are few commonly acknowledged strategies for IS investment evaluation, with much research finding that many organisations have no formal IS evolution process and lack adequate auditing techniques by which project goals can be evaluated (Primrose & Leonard, 1987;Kumar, 1990;Kennedy & Mills, 1992;Lin & Pervan, 2003;Sims et al, 2015).…”
Section: Formality In Information Systems Investment Evaluation (Isie)mentioning
confidence: 99%
“…Traditional economic evaluation techniques, such as Return on Investment, Internal Rate of Return, Net Present Value and Payback approaches, are the most commonly used methods to evaluate e-government initiatives in public sector organisations [58]. These techniques are typically based on conventional accountancy frameworks that are explicitly designed to assess the 'bottom-line' financial impact of investments.…”
Section: Evaluation Framework Based On Economic Theoriesmentioning
confidence: 99%